(untitled) (UNED Research Journal, 2024)
Introduction: Annelid polychaete worms of the family Sabellariidae build reefs by cementing together sand grains. These reefs increase local habitat heterogeneity and species diversity. The reefs are used as a refuge by invertebrates, and crustaceans are frequent. Objective: To list the species of crustaceans found in Phragmatopoma sp. reefs on two localities of the North Pacific coast of Costa Rica and at the port of Puntarenas, Gulf of Nicoya estuary. Methods: We dislodged fragments of reef colonies qualitatively at low tide with a chisel, stored them in plastic bags and later disaggregated the fragments by hand. We identified the crustaceans whenever possible and deposited them in the collection at the University of Costa Rica (MZUCR). Results: We identified 30 species: 26 species of macro-crustaceans in samples from the North coast, eight of them Petrolisthes (Porcellanidae). From the Puntarenas samples we identified five species (27 macro-crustaceans and 3 isopods). A few micro-crustaceans (Amphipoda, Isopoda) were also present but not identified. Conclusions: The number of crustacean species found in Phragmatopoma sp. reefs is relatively high but comparisons with other studies are difficult. Porcellanid crabs are common on these reefs. The low diversity of Puntarenas reefs remains unexplained.